Efektivitas Karbon Aktif Tempurung Kemiri Dalam Menurunkan Kadar Warna Naftol Merah Limbah Cair Industri Batik - Alfonsius Tripelo Fladinir; Hadi Prasetyo Suseno; Sri Sunarsih* (Jurnal Teknologi, 2022)
The batik industry is one of the producers of pollution that can damage natural ecosystems. Batik industrial wastewater contains a lot of pollutants such as conductivity, BOD, COD, TSS, TDS, oil, pH. and temperature which are not suitable for the environment. In this study, the reduction of COD, BOD. and the concentration of red naphthol dye in the batik industry wastewater which was adsorbed with activated carbon of candlenut shell was studied. Batik wastewater is taken from Ngentakrejo Village, Kapanewon Lendah, Kulon Progo Regency. Candlenut shell activated carbon was obtained from pyrolysis, sieved with a pore size of 20 mesh, 40 mesh and 60 mesh and activated with NaCl solution whose concentration varied from 1.0; 1.5; 2.0; 2.5. and 3.0 M for 16 hours. Activated carbon was applied to adsorb red naphthol on batik wastewater by varying its weight at 10; 20; 30; 40. and 50 mg. The results showed that the effectiveness of candlenut shell- activated carbon to reduce red naphthol was 12.29%, BOD 25.49% and COD 26.67%. The adsorption process with activated carbon is not recommended as a sole treatment for batik industrial wastewater.